(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Health is a fundamental need. It is also a human right to have access to high-quality health care. Due to a lack of resources, India is now dealing with a slew of health problems. This review article discusses the concept of utilizing cutting-edge technology, such as the Internet of Things, to solve health problems. It provides an architectural assessment of a smart health care system based on the Internet of Things that aims to serve everyone with high-quality health care. Patients’ bodily parameters may be measured in real time using this system design. Sensors gather patient body characteristics and send them to an Arduino Uno, which then sends the data to the cloud via a WiFI module.This information is saved in a MySql database server, which handles information and makes it accessible. The Android App may be used to see this information. Which may be installed on a smartphone, tablet, or computer? Authentication, privacy, security, and data management are all handled via cloud computing. If the data is abnormal, the patient and caretakers will be notified through email. Different decision-making algorithms may be used to make choices, and individuals can access the database based on them. The patient has access to their medical records. As a result, this system offers everyone with high-quality health care as well as error-free and seamless contact with patients.